Food Sovereignty and Indigenous Resilience: A Hermeneutic Study of Baduy’s Leuit - Ita Rodiah (Entita: Jurnal Pendidikan Ilmu Pengetahuan Sosial dan Ilmu-Ilmu Sosial, 2026)
Global food systems instability requires a rediscovery of indigenous wisdom to build community resilience. This study examines the Leuit (Baduy traditional granary) in Uten Sutendy’s novel, Baduy Sebuah Novel, focusing on its socio-religious and pedagogical roles. Using a qualitative-interpretative method grounded in cultural semiotics, this study analyzes how the Leuit serves as both a symbolic and practical tool for food sovereignty. The findings reveal that the Leuit is more than physical storage, it is a sacred site where Pikukuh (ancestral tenets) and the myth of Dewi Sri create an indigenous ethics of sustainability. These values offer a transformative framework for social studies education by providing a practical model of ecological governance. Furthermore, integrating these indigenous philosophies into the national curriculum supports Sustainable Development Goal (SDG) 2 (Zero Hunger) through decentralized, community-based food security. By repositioning the granary as a living curriculum, this study provides a critical alternative to modern consumption-driven food system, ensuring long-term national resilience